THE EFFECTS VOCABLUARY MASTERY AND LEARNING MOTIVATION TOWARDS STUDENTS’ READING COMPREHENSION AT JUNIOR HIGH SCHOOLS STATE IN PANDEGLANG - Eneng Liah Khoiriyah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2018)
The purpose of this research is to reveal whether there are significant effect of vocabulary mastery and learning motivation towards students’ Reading Comprehension. Research of hypothesis there are a significant effect of vocabulary mastery and learning motivation towards student’s reading comprehension. There are significant effects of vocabulary mastery towards student’s reading comprehension. There are significant effects of learning motivation towards student’s reading comprehension. The method used in this research was a survey. The data of vocabulary mastery and reading comprehension were acquired through multiple choice test and the data were analyzed using descriptive statistical method, multiple correlation coefficient, determination coefficient, and multiple regression analysis. The result of research concluded that: 1)There is a not significant effect of vocabulary mastery and learning motivation towards reading comprehension can be seen score Sig = 0,000 > 0,05 and Fobserved 2,893. 2.)There is a not significant effect of vocabulary mastery towards reading comprehension. can be seen score Sig = 2,85 > 0,05 and Tobserved 1,091.3).There is a not significant effect of Learning Motivations towards reading comprehension. can be seen score Sig = 1,55 > 0,05 and Tobserved 1,463.